DETERJEN ECOENZYME LOKAL: TRANSFORMASI LIMBAH NANAS UNTUK KEMANDIRIAN EKONOMI DESA TINGGIRAN DARAT - Mahdian, Mahdian; Saadi, Parham; Iskandar, Rizal; Rusmansyah, Rusmansyah; Nor Aufa, Mohamad; Khatimah, Husnul; Stevani Lase, Alvince (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2025)
Tinggiran Darat Village, Barito Kuala Regency, possesses significant pineapple production potential but faces challenges in utilizing pineapple peel waste and fluctuating market prices for pineapples. Inadequate waste management poses a risk of environmental pollution. The Community Empowerment Partnership Program (PKM) aims to empower pineapple farmers by transforming pineapple peel waste into economically valuable products, including ecoenzyme and environmentally friendly liquid detergent soap. Adopting a participatory approach based on green economy principles, the program involved 35 members of the Family Welfare Movement (PKK) and youth organizations. The proposed solutions included intensive training and continuous mentoring in the production of ecoenzyme from pineapple waste, product diversification into environmentally friendly detergents, and the introduction of effective marketing strategies. The program implementation was met with high enthusiasm from participants, evidenced by their active engagement in Q&A sessions and full involvement in practical activities. Evaluation using pre-test and post-test questionnaires demonstrated a significant increase in participants' average understanding scores. Furthermore, community perception of detergent products derived from ecoenzyme ingredients was positive. Consequently, this activity has successfully had a positive impact on the Tinggiran Darat community in managing organic waste, while fostering a sustainable economy through local innovation.